TCNSyst: A Kindergarten Information Management System for Tadika Cahaya Nurani with Data Anonymization - Khairunniesha Fadzil; Nurul Hidayah Ab Rahman (Applied Information Technology And Computer Science, 2023)
Digital transformation, often associated with the Industry Revolution 4.0 in the 21st-century, has been implemented by many industries including educational institutions. However, digital information systems could also pose security issues such as privacy leakage. Therefore, an information management system for Tadika Cahaya Nurani with data anonymization is proposed to allow admin and teacher to manage students efficiently while protecting their personally identifiable information (PII). The prototyping model was used as the methodology to develop TCNSyst with five phases which are planning, analysis, design, implementation, and testing. This web-based is developed using Atom software while MySQL as the database using JavaScript, PHP, CSS, and HTML. TCNSyst includes a login module, manage user module, manage profile module, register user module, manage timetable module, manage subject/class module, manage fee module and attendance module. Generalization technique was applied to address data and income data, while masking out technique was applied to e-mail addresses, phone number and identity card (IC) number data. Overall, TCNSyst has been successfully developed and significantly able to minimize the risk of data privacy breach